The Kill Room : A Lincoln Rhyme Novel - Deaver, Jeffery (Deaver, Jeffery. Lincoln Rhyme novel., 2013)
Renowned investigator and forensics expert, Lincoln Rhyme, is drafted to investigate the sniper-killing of a U.S. citizen in the Bahamas. While his partner, Amelia Sachs, traces the victim's steps in Manhattan, Rhyme leaves the city to pursue the sniper himself.